Stamp Down And Social Obstruction Of Power Against Muslim Women And Barrier To Education Of Zealots (International Journal of Food and Nutritional Sciences, 2022)
Muslims hold the view that Islam is not limited to certain doctrines, practices, or ceremonies. Instead, it covers every aspect of how people behave. Islam stands out among the world's active faiths because of this. Islam asserts that since it is all-encompassing, a way of life, and a thriving civilization, it has the power to improve people's liv es and teach them how to live honorably regardless of gender discrimination on both an individual and societal level. The Islamic focus on education or information acquisition is a key factor in the incentive to acquire an exceptional and ideal character. The clearest examples of the Islamic attitude to education come from the first revelation (96:1–5) and the well-known prophetic adage, "The obtaining of knowledge is a responsibility upon every Muslim" (Ibn Majah). Similar to the previous example, there are several instances when acquiring knowledge has been equally encouraged and advocated for both men and women, without regard to gender. In addition to males, women were encouraged to pursue knowledge during the time of the Prophet, according to both the holy text and Islamic history, and many of their female companions achieved greatness in a variety of fields, including the sciences of the Quran, Hadith, Fiqh, medicine, and poetry. Despite this, there is a conspicuous and spreading myth in modern society that Islam forbids women from pursuing higher education possibilities by encouraging gender prejudice.